On the $l_s$-norm Generalization of the NLS method for the Bass model (European Journal of Pure and Applied Mathematics, 2017)
The best-known and widely used model in diffusion research is the Bass model. Estimation of its parameters has been approached in the literature by various methods, among which a very popular oneÂ  is the nonlinear least squares (NLS) method proposed by Srinivasan and Mason.In this paper, we consider the $l_s$-norm $(1≤ s